Tchaikovsky and His World - Kearney, Leslie (Book collections on Project MUSE., 1998)
Caryl Emerson, Kadja Gronke, and Leslie Kearney examine a number of issues raised by Tchaikovsky's operas. Marina Kostalevsky translates Nikolai Kashkin's 1899 review of Tchaikovsky's controversial opera Orleanskaia Deva (The Maid of Orleans). The book concludes with examples of theoretical writing by Tchaikovsky and Rimsky-Korsakov, authors of Russia's first two systematic books on music theory. Lyle Neff translates and provides commentary on compositional issues that Tchaikovsky discusses in personal correspondence, as well as Rimsky-Korsakov's analysis of his own opera Snegurochka (The Snow Maiden). Tchaikovsky and His World will change how we understand the life, works, and intellectual milieu of one of the most important and beloved composers of the nineteenth century. Originally published in 1998. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.